El compromiso de la escuela en la orientación vocacional: más allá de los tests psicológicos - Flores Portal, Isabel Cristina (2014)
To talk about professional and occupational orientation, it often means tothink about a purely physiological work. The fact of taking psychotechnical,psychometric tests or interviews focused on such work, it is just a small partof what it really means the task of giving a professional and occupational guideto children and teenagers. This last point is charged, specifically, to the schoolpsychologist work; however, is a mistake to think that is just their task, as wellas thinking that vocational orientation is a work aimed to teenagers of the lastyears of secondary education, who receive this type of accompaniment. Thisarticle has the objective of reflecting the important role of the school, sincepreschool level and the subsequent levels of basic regular education, in the taskof guiding learners in the vocational level; as well as, emphasizing the directrelation between a conscious and comprehensive election of the selectedvocation and the harmonious development of an entire society and, with it, theeconomic benefit of a country.